2021
DOI: 10.5194/essd-2021-137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global sea-level budget and ocean-mass budget, with focus on advanced data products and uncertainty characterisation

Abstract: Abstract. Studies of the global sea-level budget (SLB) and the global ocean-mass budget (OMB) are essential to assess the reliability of our knowledge of sea-level change and its contributions. Here we present datasets for times series of the SLB and OMB elements developed in the framework of ESA's Climate Change Initiative. We use these datasets to assess the SLB and the OMB simultaneously, utilising a consistent framework of uncertainty characterisation. The time series, given at monthly sampling, include gl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 85 publications
0
16
1
Order By: Relevance
“…Our total uncertainty in the regional barystatic sea-level trend ranges from 0.62 to 1.02 mm.year −1 for 2003-2016, and from 0.37 to 0.75 mm.year −1 for 1993-2016 for the IMB+WGP combination, with spatial averages of 0.80 and 0.47 mm.year −1 , respectively. While these values may seem large compared to studies focusing on global changes alone (Horwath et al, 2021;Frederikse et al, 2020), other studies also found that regional uncertainties are higher than the previously published global mean rates (Prandi et al, 2021;Bos et al, 2014). For example, in a recent satellite altimetry sea-level change assessment, Prandi et al (2021) found that the local sea-level trend uncertainty due to observational errors (i.e., intrinsic uncertainties) was about two times higher than the global mean sea-level trend uncertainty of Ablain et al (2019).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our total uncertainty in the regional barystatic sea-level trend ranges from 0.62 to 1.02 mm.year −1 for 2003-2016, and from 0.37 to 0.75 mm.year −1 for 1993-2016 for the IMB+WGP combination, with spatial averages of 0.80 and 0.47 mm.year −1 , respectively. While these values may seem large compared to studies focusing on global changes alone (Horwath et al, 2021;Frederikse et al, 2020), other studies also found that regional uncertainties are higher than the previously published global mean rates (Prandi et al, 2021;Bos et al, 2014). For example, in a recent satellite altimetry sea-level change assessment, Prandi et al (2021) found that the local sea-level trend uncertainty due to observational errors (i.e., intrinsic uncertainties) was about two times higher than the global mean sea-level trend uncertainty of Ablain et al (2019).…”
Section: Discussionmentioning
confidence: 87%
“…Fingerprints of barystatic SLC have been the subject of several studies, ranging from investigating the effects of variations in paleoclimate, for example the SLC due to the last deglaciation event (Lin et al, 2021), to contemporary SLC (Frederikse et al, 2020). Most of the studies including presentday barystatic SLC have focused either on the GRACE satellite period (since 2002) (Bamber and Riva, 2010;Riva et al, 2010;Hsu and Velicogna, 2017;Adhikari et al, 2019;Frederikse et al, 2019), on the closure of the sea-level budget over a longer period (Slangen et al, 2014;Frederikse et al, 2020) or on the barystatic contribution to global mean SLC (Chambers et al, 2007;Horwath et al, 2021). However, an in-depth analysis of regional barystatic SLC and its uncertainties during the satellite altimetry era (since 1993) has not yet been done.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of studies have investigated the closure of the sea-level budget at global and regional scales over the altimetry era [1][2][3][4][5]. This is generally carried out by comparing the altimetry-based sea-level change with the sum of contributions using observations (e.g., Gravity Recovery and Climate Experiment (GRACE) satellite gravimetry data for estimating mass changes, and Argo-based ocean temperature and salinity data) or model outputs (e.g., for estimating glacier mass balance).…”
Section: Introductionmentioning
confidence: 99%
“…This is generally carried out by comparing the altimetry-based sea-level change with the sum of contributions using observations (e.g., Gravity Recovery and Climate Experiment (GRACE) satellite gravimetry data for estimating mass changes, and Argo-based ocean temperature and salinity data) or model outputs (e.g., for estimating glacier mass balance). Assessing the closure/nonclosure of the sea-level budget has many implications, such as detecting acceleration [2] or an abrupt change in one or several components, for process understanding [5], cross calibrating the different observing systems used to quantify sea-level and its components, detecting possible systematic errors [6,7], placing upper bounds on poorly determined or missing contributions (e.g., from the deep ocean not sampled by Argo [8]), and finally for validating climate models used to simulate future changes. In terms of global average, the sea-level budget is found to be closed up to around 2016 within the observation uncertainties (e.g., [1][2][3][4][5]), although beyond 2016, the global mean budget appears no longer closed [6,7].…”
Section: Introductionmentioning
confidence: 99%